Classificação facetada em odontologia - Rosa, Malvina Vianna (1972)
Bibliographical classifications cre considered as related to retrieval language. The importance of faceted classification for special subjects. 250 titles on dentistry, were analysed. The terms, then got, were arranged into facets. There are five basic facets: OPERATIONS, AGENTS, ANATOMY & PHYSIOLOGY, PATHOLOGY, PATIENTS. Within the facets the terms were organized into arrays. The best citation order, in accordance with researcher’s thought, was determined. The filing order is inverted in relation to citation order. An ordinal notation was added to the system. The efficiency of the system was avaluate through 40 titles classification, a chain index of 10 titles and the construction of a thesaurus, exemplified with 8 terms. It was demonstrate the high degree of specification reached by the system.